Faktor-Faktor yang Berhubungan dengan Lama Penyembuhan Luka Diabetes Mellitus Tipe II di Kota Batam - Angelina Jessica Simbolon; Utari Christya Wardhani; Sri Muharni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Increased blood sugar levels due to the body's impaired insulin production are a sign of a chronic metabolic disease known as diabetes mellitus. As seen in Batam, cases of diabetes mellitus in Indonesia are relatively high. This study aims to determine how long type II diabetes mellitus wounds last in Batam City. This study used a cross-sectional approach to conduct quantitative descriptions. This study involved 60 people. The Chi-Square test was used to conduct data analysis. The results showed that there was a significant correlation between age and the healing time of diabetes mellitus wounds, with a sig P value of 0.001 <0.05; gender had a significant correlation, with a sig P value of 0.007 <0.05; sugar control had a significant correlation, with a sig P value of 0.001 <0.5; and anemia had a significant correlation, with a sig P value of 0.001 <0.5. The results indicate that there is a relationship between these variables and the healing time of type II diabetes mellitus wounds. It is hoped that this study can be used as literature for further research.